Cassava and turmeric flour blends as new raw materials to extruded snacks - Spinello, Alessandra Mussato [UNESP]; Leonel, Magali [UNESP]; Mischan, Martha Maria [UNESP]; Carmo, Ezequiel Lopes Do [UNESP] (Editora da Universidade Federal de Lavras (UFLA), 2014)
Short cooking time and ability to blend varieties of food ingredients have made extrusion cooking a medium for low-cost and nutritionally improved food products. The effect of moisture, extrusion temperature and amount of turmeric flour mixed with cassava flour on physical characteristic of puffed snacks was evaluated in this work. Extrusion process was carried out using a single-screw extruder in a factorial central composite design with four factors. Results showed effect of extrusion parameters on dependents variables. High expansion, low browning, low water solubility index, intermediate water absorption index and high crispness desirable characteristics to puffed snacks are obtained in conditions of 12% moisture, 5% turmeric flour, 105º C of temperature and 250 rpm of screw speed. These paper point to the potential still unexplored of the use of flours of cassava and turmeric as raw materials in the development of extruded puffed snacks.

O curto tempo de cozimento e capacidade para misturar vários ingredientes fizeram da extrusão um meio para o desenvolvimento de produtos alimentares de baixo custo e nutricionalmente melhorados. Neste trabalho foram avaliados os efeitos da umidade, da temperatura de extrusão e da quantidade de farinha de açafrão misturada com a farinha de mandioca nas características físicas de snacks expandidos. O processo de extrusão foi realizado em um extrusor monorrosca, utilizando o delineamento central composto rotacional com quatro fatores. Os resultados mostraram efeito dos parâmetros de extrusão sobre as variáveis dependentes. Alta expansão, baixo escurecimento, baixo índice de solubilidade em água, índice de absorção de água médio e elevada crocância, características desejáveis para snacks extrusados, podem ser obtidas em condições de 12% de umidade, 5% de farinha de açafrão, 105º C de temperatura e 250 rpm de rotação do parafuso. Esses resultados apontam para o potencial ainda pouco explorado do uso de farinhas de mandioca e açafrão como matéria-prima para o desenvolvimento de snacks.
Misturas de farinhas de mandioca e de açafrão como novas matérias-primas para snacks extrusados
Keywords: Curcuma longa; Manihot esculenta; extrusão; Curcuma longa; Manihot esculenta; extrusion